Prognostic and predictive factors of brain meningiomas - Palička, M; Wozniaková, M; Knybel, L; Cvek, J (Klinicka onkologie, 2022)
BACKGROUND: Common primary brain tumors are meningiomas with year incidence 3-8 cases per 100 000 people. Even though we mainly speak about benign disease, with its character and localization, it worsens the life quality to its bearer. The main therapeutic methods are neurosurgery extirpation and stereotactic radiosurgery. Despite reaching very good therapeutic results with both methods, some of the patients suffer with recurrence of the disease requiring other interventions with the risk of creating or worsening a neurological deficit. Small meningiomas without growing tendency and with the absence of symptomatology are observed. On the other hand, we cannot be satisfied with long-term results of the therapy of meningiomas with more aggressive bio-logical behavior. A higher grade is a known risk of meningioma recurrence; however, it is often difficult to identify subgroups that show advantage of a combination of neurosurgery and radiosurgery, respectfully at which it is appropriate to look for ways to treatment escalation, and that is with the risk of side effects. The analysis of hormonal, cytogenetics and epigenetics tumor equipment seems to be the most promising for the development of personalized treatment. PURPOSE: The aim of this work is to sum up the facts about epidemiology, treatment algorithms and the prognosis of brain meningiomas and to suggest perspective prognostic and predictive factors for maximally individualized therapy.
Keywords: meningeom; Prognosis; mozek; Epigenetics; retrospektivní studie; Humans; Brain; Meningioma; Meningeal Neoplasms; Stereotactic radiosurgery; prognóza; radiochirurgie; meningeální nádory; výsledek terapie; Treatment Outcome; Cytogenetics; cytogenetics; lidé; meningeoma; Radiosurgery; Retrospective Studies